Comportamiento de las estructuras de madera construidas en la Estancia Jesuítica de Santa Catalina en el siglo XVII - Gómez, J. L.; Fernández Saiz, M. del C.; Papalardo, L. (Revista ALCONPAT, 2014)
This paper presents a study of wooden structural typologies used by the Jesuits in the "Estanciade Santa Catalina", Córdoba Province. The wood used in beams and columns was characterizedat microscopic and macroscopic levels. Tests were carried out to determine the physical andmechanical characteristics; the soundness of the structure was evaluated by following theBrazilian standard BR7190 for the verification of the strength and deformability. We studiedthe reticulated structures, showing the pathological manifestations in the structural elementsand making a diagnosis that allowed the estimation of their degree of safety. The studyhighlights the outstanding durability of the wood older than 360 years; it also recommendsproceedings for the recovery of damaged parts and maintenance of these constructions thathave been declared common heritage of mankind.Keywords: Wooden Structures, patrimony, heritage durability